Marxism in the built environment in Poland: its contribution and legacy - Gorzym-Wilkowski Waldemar A. (Bulletin of Geography: Socio-Economic Series, 2017)
Due to its tangible character, the built environment constitutes a lasting evidence of past and present socio-economic phenomena. In Poland, these phenomena were developing for several decades according to the principles of Marxist ideology and its consequences. As a result, the built environment in Polish urban and rural areas was shaped by Marxist concepts and the resulting realities of centrally planned economy. Multi-family housing projects, vast and neglected post-industrial areas and monotonous, styleless buildings in rural areas are the main remnants of the period of what was known as “real socialism”. The effects of Marxism on the built environment in Poland are mostly negative in economic and social terms, and the efforts to eliminate these effects often fail to improve the situation. Therefore, the legacy of Marxism in Polish space will still be visible for many years to come.